High prevalence and risk factors of undernutrition in adult cancer patients at Hawassa University Hospital: a call for targeted interventions - Worku, Simret Girma; Wondimagegne, Zelalem Tafese (PeerJ, 2025)
Background Cancer, a condition marked by the uncontrolled growth of abnormal cells, remains a major global health concern and is the second most common cause of death worldwide. Both the disease itself and its treatments can negatively impact taste, smell, appetite, and nutrient absorption, increasing the risk of malnutrition. This study aimed to determine the prevalence and factors associated with undernutrition among adult cancer patients, with the goal of identifying key characteristics that could inform targeted interventions to address nutritional challenges in this population. Method A cross-sectional study involving 393 participants was conducted at a hospital using a convenient sampling method. Data collection took place over a two-month period from April to June 2023 through face-to-face interviews, utilizing a structured questionnaire. Quantitative data were gathered using both the questionnaire and the Patient-Generated Subjective Global Assessment short form (PG-SGA-SF). Data were analyzed with SPSS version 20, applying both bivariate and multivariate logistic regression analyses to identify associated factors. Variables with a p-value less than 0.05 were considered statistically significant predictors. Results Based on the PG-SGA-SF score, 58% of cancer patients were found to be malnourished. According to BMI measurements, 21% of participants were classified as underweight, while over 41% reported low dietary diversity, and nearly 78% were in advanced stages (III and IV) of cancer. Undernutrition showed significant associations (p < 0.01) with BMI below 18.5 kg/m2 (AOR = 2.81, 95% CI [1.29–6.08]), poor dietary diversity (AOR = 4.54, 95% CI [2.41–8.53]), consumption of semisolid and liquid diets (AOR = 4.41, 95% CI [2.41–8.10]), presence of nausea (AOR = 10.71, 95% CI [5.48–20.94]), and constipation (AOR = 6.42, 95% CI [2.95–13.97]). Conclusion The findings of this study reveal a considerable burden of undernutrition among adult cancer patients, emphasizing the critical need for routine nutritional screening as part of cancer care. Early identification of malnutrition is essential to effectively manage associated symptoms, prevent nutrition-related complications, and improve treatment outcomes. Integrating comprehensive nutritional assessment and support into oncology services is recommended to enhance the quality of care and overall prognosis for cancer patients.
Keywords: Cancer; Malnutrition; Constipation; Diet Diversity; Nausea; Vomitting; Patient Generated-Subjective Global Assessment; Nutrition; Disease; Predictors